QUALITY IMPROVEMENT OF MIN 1 YOGYAKARTA - Nasrin Nabila (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2020)
This study examines strategies for improving the quality of schools in MIN 1 Jogja. The focus of discussion in this research is what is meant by the quality of education, what is the quality standard of education in Indonesia, and how is the quality improvement strategy in MIN 1 Yogyakarta. This research uses a qualitative research approach, with research methods in the field study. The results of this study indicate that the strategy of improving quality in MIN 1 Yogyakarta as a whole is trying as much as possible to carry out all the process activities in MIN 1 Yogyakarta in accordance with UU No. 20 of 2003 concerning the National Education System in Chapter IX, namely 8 quality standards of education and additional programs in the form of five achievements, wherein the quality improvement will be carried out gradually but continuously